An air-pressure-free elastomeric valve for integrated nucleic acid analysis by capillary electrophoresis. (20th October 2015) - Jung, Wooseok; Barrett, Matthew; Brooks, Carla; Rivera, Andrew; Birdsell, Dawn N; Wagner, David M; Zenhausern, Frederic
Abstract: We present a new elastomeric valve for integrated nucleic acid analysis by capillary electrophoresis. The valve functions include metering to capture a designated volume of biological sample into a polymerase chain reaction (PCR) chamber, sealing to preserve the sample during PCR cycling, and transfer of the PCR-products and on-chip formamide post-processing for the analysis of DNA fragments by capillary gel electrophoresis. This new valve differs from prior art polydimethylsiloxane (PDMS) valves in that the valve is not actuated externally by air-pressure or vacuum so that it simplifies a DNA analysis system by eliminating the need for an air-pressure or vacuum source, and off-cartridge solenoid valves, control circuit boards and software. Instead, the new valve is actuated by a thermal cycling peltier assembly integrated within the hardware instrument that tightly comes in contact with a microfluidic cartridge for thermal activation during PCR, so that it spontaneously closes the valve without an additional actuator system. The valve has bumps in the designated locations so that it has a self-alignment that does not require precise alignment of a valve actuator. Moreover, the thickness of the new valve is around 600 μ m with an additional bump height of 400 μ m so that it is easy to handle and very feasible to fabricate by injection molding compared to other PDMS valves whose thicknesses are around 30–100 μ m. The new valve provided over 95% of metering performance in filling the fixed volume of the PCR chamber, preserved over 97% of the sample volume during PCR, and showed very comparable capillary electrophoresis peak heights to the benchtop assay tube controls with very consistent transfer volume of the PCR-product and on-chip formamide. The new valve can perform a core function for integrated nucleic acid analysis by capillary electrophoresis.